OPTIMASI PROSES PRODUKSI BIODIESEL JARAK PAGAR MELALUI TRANSESTERIFIKASI IN SITU - Ika Amalia Kartika,Ariska Duti Lina, Ono Suparno, Dede Hermawan (Department of Agroindustrial Technology, Bogor Agricultural University, 2016)
Jatropha seed is potential to be utilized as raw material for biodiesel production by in situ transesterification because of its high oil content (30%). The objective of this research was to optimis reaction time and hexane to total solvent ratio in biodiesel production from jatropha seed by in situ transesterification, and to analyze the influence of reaction time and hexane to total solvent ratio on biodiesel yield and quality. The research was designed using Central Composite Design, and the in situ transesterification process was carried out at 400 rpm stirring speed and 50°C reaction temperature with potassium hidroxice (KOH) concentration of 0.075 mol/L in methanol. The process conditions were optimized using Response Surface Method with reaction time (4-10 h) and hexane to total solvent ratio (0.01-0.416) as their process variables, and the responses measured were biodiesel yield, density, viscosity, acid, saponification and ester values. The optimum process conditions to produce biodiesel from jatropha seed by in situ transesterification were obtained at 7.08 h reaction time and 0.32 hexane to total solvent ratio. For these process conditions, the optimum biodiesel yield was 57.4% with acid value of 0.48 mg KOH/g, saponification value of 281.7 mg KOH/g, ester value of 281.3 mg KOH/g, viscosity of 3.60 cSt and density of 0.67 g/cm3. The effect of process conditions on biodiesel yield was significant, especially hexane to total solvent ratio. However their effect on biodiesel quality is not important. Keywords: biodiesel, in situ transesterification, jatropha, optimization, response surface method